Up-regulation of Tim-3 Expression Contributes to Development of Burn-induced T Cell Immune Suppression in Mice - 唐朝晖 余彦 邱文洪 张剑 杨想平 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
T cell immunoglobulin and mucin domain 3 （Tim-3） is well known to negatively regulate T cells responses, but its role in burn-induced T cells immune suppression remains unclear. In the present study, in order to identify the relationship between Tim-3 expression and post-burn T cells immune suppression, C57BL/6 mice were subjected to burn injury or sham injury, and the liver and spleen were harvested at the day 1 after operation. The expression level of Tim-3 on hepatic or splenic T cells and the functional properties of Tim-3＋ T cells were evaluated. It was found burn injury induced dramatically elevated Tim-3 expression on both hepatic and splenic CD4＋ and CD8＋ T cells in contrast with the post-burn depletion of T cells. Furthermore, Tim-3 expression was correlated with the suppressive phenotype of T cells following burn injury, including increased expression of anti-inflammatory cytokine IL-10, decreased expression of pro-inflammatory cytokines IFN-γ and TNF-α, reduced T cell proliferation and elevated co-expression of Tim-3 and PD-1. Moreover, Tim-3＋ T cells subsets were more prone to spontaneous apoptosis than Tim-3- T cells subsets. Our findings reinforce the idea that the up-regulated expression of Tim-3 on T cells after burn injury plays an important role in the development and maintenance of burn-induced T cell immune suppression.